Simple cholecystectomy versus radical resection for stage Ⅱ gallbladder cancer: a meta-analysis - Cheng, Zheng-jun; Qiu, Chan; Li, Da-xing; Gong, Jian-ping; Cheng, Qian (International Surgery Journal, 2017)
Background: GBC was first reported more than two hundred years ago, but the poor therapeutic effect for GBC patients is still frustrating now, the 5-year survival rate is no more than 5%, and the mean survival time is only about half a year. The objective of this study was to evaluate the importance of radical resection in the treatment of Nevin II and T1b stage gallbladder cancer (stage II GBC) by analyzing the survival rate and tumor recurrence rate after accepting simple cholecystectomy (SC) and radical resection (RR). Methods: PubMed, Embase, Chinese National Knowledge Infrastructure and Wanfang databases was searched from inception to February 2016. Quality assessment was conducted in each of the available studies by using the validated Newcastle-Ottawa Quality Assessment Scale (NOS) for cohort and case-control studies. Publication bias was also assessed by using a funnel plot. The odds ratio (OR) and its 95% confidence interval (95% CI) were employed to estimated effect size. All statistical analyses were carried out using Rev Man 5.2 software. Results: A total of fifteen studies encompassing 424 patients meeting the search criteria were included. Pooled analyses revealed that comparing to simple cholecystectomy, radical resection can significantly increase the 1-, 3- and 5-year survival rate of patients with stage IIGBC (OR = 3.28, 95% CI: 1.83-5.89, P<0.0001; OR = 2.52, 95% CI: 1.49-4.28, P = 0.0006; OR = 3.19, 95% CI: 1.85-5.51, P<0.0001), and patients after radical resection have a significant lower tumor recurrence rate (OR = 0.30, 95% CI: 0.11-0.80, P = 0.02). Conclusions: The short- and long-term survival rate of patients with stage II GBC following radical resection is obviously higher than that of patients receiving simple cholecystectomy, and the tumor recurrence rate is obviously lower. Radical resection would be a better choice for stage IIGBC.